University challenges: reforming the reform - Zarate, Eduardo (2013)
The authors review the University of Cordoba reform initial concepts, its validity and the new university crisis having both liberal politics and knowledge globalization as framework. We propose debate models for reforming the reform and the public university mission to give knowledge as a public right. In addition we discuss the administrative models and research challenges needed to modify production procedures in Peruvian public universities.